Situation Report: Yugoslavia, 16 October 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Slovenian Journalists Reject Marxism-Leninism / by Slobodan Stankovic Trading Ideological Blows / by Slobodan Stankovic Yugoslav Press Critical of Eastern Europe / by Slobodan Stankovic Belgrade Weekly Criticizes Quadhafi [Qaddafi] / by Slobodan Stankovic